COMPARISON OF THE PROPORTIONS OF THE VERB IN COMBINATION AND GAIN IN UZBEK, RUSSIAN AND KARAKALPAK LANGUAGES - Usanova Qademay Muratbay qizi (Western European Studies, 2024)
In this article, the comparison of the verb word category in Uzbek, Russian and Karakalpak languages, verb proportions: conjugation and gain ratios, their similarities and differences were studied
Keywords: verb word category; verb ratios; degree